A first case of hepatocellular carcinoma in the baboon (Papio spp.) placenta. Issue 1 (24th September 2018) - Schlabritz‐Loutsevitch, Natalia; Carrillo, Maira; Li, Cun; Nathanielsz, Peter; Maguire, Christopher; Maher, James; Dick, Edward; Hubbard, Gene; Stanek, Jerzy
Abstract: We present a case of hepatocellular carcinoma (HCC) in the placenta of healthy baboon ( Papio spp .). Grossly, the fetal, maternal, and placental tissues were unremarkable. Histologically, the placenta contained an unencapsulated, poorly demarcated, infiltrative, solidly cellular neoplasm composed of cells that resembled hepatocytes. The neoplastic cells were diffusely positive for vimentin and focally positive for Ae1/Ae3, Arginase ‐1, glutamine synthetase, and CD10, and negative for ER, vascular markers (CD31 and D240), S100, glypican, C‐reactive protein, FABP, desmin, and beta‐catenin; INI1 positivity was similar to non‐neoplastic tissues. The case likely represents a unique subtype of HCC.